Design and implementation of a driver circuit for three-phase induction motor based on STM32F103C8T6 - Salih, Nahla Abdul Jalil; Altaie, Hayder Tareq Rajab; Al-Azzawi, Waleed Khalid; Mnati, Mohannad Jabbar (Bulletin of Electrical Engineering and Informatics, 2023)
A three-phase induction motor is an electrical machine that can be used for many industrial applications. A three-phase driver circuit, also known as a three-wire series circuit or three-wire delta circuit is an electrical power system. These motors typically rely on power supplied using electric cables, which carry alternating currents. The three-phase motor inverter driver circuit is a simple circuit consisting of three half-wave rectifiers, which are connected in a bridge. When the input voltage level of the DC power supply to the inverter is high enough, this arrangement can provide a large current through the induction motor. This paper will show how to build a three-phase inverter driver circuit from scratch for a threephase induction motor by using (transistors and diodes) for photovoltaic application. The paper will guide people through each step with diagrams and schematics that make it easy for anyone to understand every part of this project and ensure people's safety by learning how these components work before putting them into their own design. The focus of this project will be on the use of STM32F103C8T6 as microcontrollers to generate the pulse width modulation (PWM) signals.